Trigonelline exerts its neuroprotective effects in experimental spinal cord injury through modulation of inflammation, apoptosis, and neurotrophic factors - Zhi-Lan Ye; Yuan Cao (Asian Pacific Journal of Tropical Biomedicine)
Objective: To assess the protective effects of trigonelline against spinal cord injury (SCI) in rats. Methods: Rats (Sprague-Dawley, male) were randomly assigned to seven groups (n=15 per group): normal, sham, SCI control (1% DMSO), methylprednisolone (30 mg/kg), and trigonelline (50, 100, and 200 mg/kg). Rats received respective treatment daily for 28 days. SCI was induced by using a temporary aneurysm clip. Behavioral, biochemical, and histological analyses were performed to investigate the neuroprotective effect of trigonelline. Results: Trigonelline (100 and 200 mg/kg) treatment effectively (P<0.05) mitigated SCI-induced changes in mechano-tactile sensation, allodynia, hyperalgesia, and motor nerve conduction velocity. It notably (P<0.05) downregulated apoptotic (Bax and caspase-3) and inflammatory (COX-II) markers, while upregulating Bcl-2 and BDNF mRNA expression in the spinal cord (P<0.05). Furthermore, trigonelline effectively alleviated (P<0.05) SCI-induced alterations in mitochondrial complex levels, resulting in enhanced nicotinamide adenine dinucleotide dehydrogenase, succinate dehydrogenase, redox activity, and cytochrome-C levels. Histological examination of spinal cord tissue indicated that trigonelline significantly (P<0.05) ameliorated the histological damage caused by SCI, thereby improving neuronal degeneration, inflammatory cell infiltration, and necrosis. Conclusions: Trigonelline shows neuroprotective properties in SCI rats by reducing allodynia, hyperalgesia, and inflammation, stabilizing mitochondrial enzyme complexes, and modulating apoptotic and neurotrophic factors. Thus, trigonelline holds promise as a potential neuroprotective agent.